Le maraîchage : révélateur du dynamisme des campagnes sahélo-soudaniennes - Stéphane Bastin; Audrey Fromageot (Belgeo)
By appearing at the end of the small-irrigation development programs wich were initiated at the beginning of the 80s by the governments of Niger and Ivory Coast, the expansion of market gardening in the Songhay and Senufo areas seems to have been directly induced by them. Which would confirm the afro-pessimist conviction that the african farmers are no more able to take part in their own development. However, the facts that the emergence of market gardening hasn’t closely followed the launchning of such programs and that its diffusion has occurred in contexts of decreasing investments to the agricultural sector tend to show that the development process of this new type of commercial agriculture doesn’t correspond to an exogenous dynamic. In fact, this development must be seen as a result of farmers’ ability to mobilize their technical inheritances when – at the beginning of the 90s – they became obliged to diversify their village-based income sources to answer the structural crisis encountered by the main food-producing and commercial agricultures.